Теоретичні аспекти інвестиційної активності підприємств - Самодурова, Д.А. (Стратегія і механізми регулювання промислового розвитку, 2016)
Визначено сутність інвестиційної активності підприємств. Розглянуто показники та методи оцінки інвестиційної активності підприємств. Проаналізовано інвестиційну активність підприємств України в останні роки. Определена сущность инвестиционной активности предприятий. Рассмотрены показатели и методы оценки инвестиционной активности предприятий. Проанализирована инвестиционная активность предприятий Украины в последние годы. The article explains the purpose of the enterprises investment activity. Indicators and evaluation methods of investment activity of enterprises are considered in the article. Investment activity of enterprises Ukraine in recent years is performed. Today the topic of investment activity of enterprises is of great interest among scientists. This is due to the fact that in modern economic conditions, enterprises cannot exist and develop only at the expense of their own resources. A number of production problems, such as obsolete production facilities, lack of innovation in production, non-competitiveness of most of domestic industrial products require the attraction of investment resources. The characteristic of investment intensity determines the investment activity of the enterprise. At the present stage, investment activity is the interaction of internal and external factors of enterprise activity. Where internal factors are investment opportunities, external - investment processes and investment climate.The analysis of the investment activity of domestic enterprises for certain types of industrial activity makes it possible to conclude that it is necessary to intensify investment activity at all levels.